2019
DOI: 10.1177/2165079919827042
|View full text |Cite
|
Sign up to set email alerts
|

Which Factors Influence Farmers’ Use of Protective Measures During Pesticides Exposure?

Abstract: Farmers in developing countries use harmful pesticides while taking few or no protective measures. There is limited evidence on factors affecting their safety measures. The objective of this study was to identify the underlying factors influencing farmers’ protective behaviors (PBs) and use of personal protective equipment (PPE) during the exposure to pesticides. From April to August 2017, a descriptive study was conducted in Twiserkan County in western Iran among 474 farmers from 104 villages. A questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 43 publications
7
28
0
1
Order By: Relevance
“…The results also showed that farmers' expectation to produce more positively affected their intention to engage in unsustainable behavior. This is in line with findings of Maddux et al (1982) and Afshari et al (2019). The indirect effect of subjective culture on unsustainable behavior through farmers' intention showed that despite the destructive effect of unsustainable agriculture, more cultural intervention is needed to motivate farmers to use more environmentally friendly methods in their farm production methods.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results also showed that farmers' expectation to produce more positively affected their intention to engage in unsustainable behavior. This is in line with findings of Maddux et al (1982) and Afshari et al (2019). The indirect effect of subjective culture on unsustainable behavior through farmers' intention showed that despite the destructive effect of unsustainable agriculture, more cultural intervention is needed to motivate farmers to use more environmentally friendly methods in their farm production methods.…”
Section: Discussionsupporting
confidence: 87%
“…This in turn would encourage wider rural farmers to apply proper standards known as Good Agricultural Practices (GAP) in their farm production. (Afshari et al, 2019). The results of the study indicated that contextual factors such as culture, educational level, and socio-political status of farmers influenced unsustainable behavior among farmers (Afshari et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the effective use of these SPMs depends on an individual's mindset. Factors including an individual's age, knowledge, risk perception, belief, social and norms influence, perceived benefits and barriers influence the use of SPMs and their engagement in safe behaviors [4]. Identifying the impact of these factors on SPMs will provide better insight into individuals to follow safety behaviors [5].…”
Section: Introductionmentioning
confidence: 99%